ii ANALISIS TINGKAT HAK DAN AKSES DALAM PROGRAM PENGELOLAAN HUTAN BERSAMA MASYARAKAT (PHBM) DI DESA DAGANGAN, KABUPATEN MADIUN - , EGA PRADIPTA ARMANDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
During the New Order regime, the government more prioritized development of urban centers than rural development. Unequal development leads to unequal economic growth which is concentrated in the urban, and leaves rural areas less developed. One of the objectives to be achieved in community forestry is poverty aleviation of forest people by improving their social welfare. Social welfare improvement could be achieved through grand thing more access to the forest through PHBM program. The objective of this research is to comprehend community rights and access levels before and after PHBM program. The research aimed to compare access levels before and after the implementation of PHBM. This research was conducted in LMPSDH Wana Salam, Dagangan Village, Madiun District. This research was approach through quantitative research with survey method. Data were collected through interviews using questionnaire, observations, and collection of secondary data. Quantitative descriptive analysis method was employed for data analysis. The results of the research indicate that levels of community rights in Dagangan Village over forest resources increase. Prior to the implementation of local people head to types of rights: access and utilization rights. However, the ability of the people to access the forests declines to a certain degree. The declines related to the deminishing forest practices deemed to as illegal.